2023
DOI: 10.2196/44465
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Self-Reported COVID-19 Vaccination Status Compared With a Public Health Vaccination Registry in Québec: Observational Diagnostic Study

Patrick M Archambault,
Rhonda J Rosychuk,
Martyne Audet
et al.

Abstract: Background The accuracy of self-reported vaccination status is important to guide real-world vaccine effectiveness studies and policy making in jurisdictions where access to electronic vaccine registries is restricted. Objective This study aimed to determine the accuracy of self-reported vaccination status and reliability of the self-reported number of doses, brand, and time of vaccine administration. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Although the information on vaccinations and infection was self-reported, the participants were all HCWs who may be more accurate in their reporting than the general population. Previous studies have shown that, in patients, self-report of vaccination status was very largely concordant with vaccination records but that self-reported dates and type of vaccine were less accurate [24] [25]. In the current study public health records were accessed for a majority of the serology sub-cohort and the congruence in estimates using purely self-report episodes and episodes corrected from external records gives some confidence to the findings for the serology cohort overall.…”
Section: Discussionmentioning
confidence: 67%
“…Although the information on vaccinations and infection was self-reported, the participants were all HCWs who may be more accurate in their reporting than the general population. Previous studies have shown that, in patients, self-report of vaccination status was very largely concordant with vaccination records but that self-reported dates and type of vaccine were less accurate [24] [25]. In the current study public health records were accessed for a majority of the serology sub-cohort and the congruence in estimates using purely self-report episodes and episodes corrected from external records gives some confidence to the findings for the serology cohort overall.…”
Section: Discussionmentioning
confidence: 67%
“…Self-reported COVID-19 vaccination status appears to have good accuracy. [15][16][17][18] Participants rated 15 items regarding their attitudes toward the COVID-19 pandemic, the COVID-19 vaccine, and a possible vaccine mandate; 11 of the questions were from national surveys 12,13 and 4 were added to investigate concern about COVID-19, perceived quality of public health messaging, and support from family and friends. They also rated the trustworthiness of 11 sources of information on the COVID-19 vaccine (eg, family, friends, medical professionals, social media, US President); 9 questions were from a national survey 10 and 2 additional questions assessed the possible impact of celebrities and the US President on COVID-19 vaccine opinions.…”
Section: Methodsmentioning
confidence: 99%
“…Crude (perceived risk only) agreement between the two [47][48][49]. Further, selfreported health conditions [50] and use of medication [51] have been found to have high specificity and moderate sensitivity; thus, we may have underestimated the prevalence of health conditions or oral antiviral use.…”
Section: Covariates Included In Models*mentioning
confidence: 99%